A study of epidemiological determinants and quality of life in physically differently abled persons attending physical medicine and rehabilitation center in a Metropolitan city - Rajesh Katre; Rohan Sangam; Mridula Solanki; Shalini Rawat (Indian Journal of Community and Family Medicine)
Background: The quality of life (QOL) among individuals with physical disabilities is a critical and multifaceted aspect of well being that encompasses the various dimensions of their lived experiences. Aims and Objectives: The present study was undertaken to understand the epidemiology and QOL and factors affecting it among people living with physical disability. Material and Methods: It was a cross sectional and observational study conducted among beneficiaries attending physical medicine and rehabilitation center in a metropolitan city. The sample size was calculated to be 177, and participants were enrolled using the convenient sampling method. The World Health Organization WHO BREF scale was used to assess QOL. SPSS software version 21.0 and Microsoft Excel were used to analyze the data. Results: It was observed that most of the participants were unemployed (52.5%) and belonged to middle class (class 3) (34.5%) of the B.G Prasad Socioeconomic Scale. 52.5% have had disability for more than 20 years, with the major cause of disability being infective etiology (44.4%) followed by traumatic (27.1%) and congenital (15.8%). The disability was majorly seen in the lower limb (61.6%), which caused hinderance in walking in majority of the participants (90.1%). 57.6% reported that they had a good QOL, 67.8% were satisfied with their health and mean scores for physical and environmental domain were 68.05 and 50.85. Conclusion: Education, employment, and involvement of spine had a significant association with overall QOL. Disability had a profound effect on the QOL; environmental, social, and psychological were the most affected domains observed. Employment and education spinal involvement had a significant impact on QOL. Infective etiology was the most common cause of disability, while lower limb was the most affected body part.